Health-related quality of life, neuropsychiatric symptoms and structural brain changes in clinically isolated syndrome. - Eva Hyncicova; Adam Kalina; Martin Vyhnalek; Tomas Nikolai; Lukas Martinkovic; Jiri Lisy; Jakub Hort; Eva Meluzinova; Jan Laczó (PLoS ONE)
Background Neuropsychiatric symptoms and reduced health-related quality of life (HRQoL) are frequent in multiple sclerosis, where are associated with structural brain changes, but have been less studied in clinically isolated syndrome (CIS). Objective To characterize HRQoL, neuropsychiatric symptoms (depressive symptoms, anxiety, apathy and fatigue), their interrelations and associations with structural brain changes in CIS. Methods Patients with CIS (n = 67) and demographically matched healthy controls (n = 46) underwent neurological and psychological examinations including assessment of HRQoL, neuropsychiatric symptoms and cognitive functioning, and MRI brain scan with global, regional and lesion load volume measurement. Results The CIS group had more, mostly mild, depressive symptoms and anxiety, and lower HRQoL physical and social subscores (p≤0.037). Neuropsychiatric symptoms were associated with most HRQoL subscores (β≤-0.34, p≤0.005). Cognitive functioning unlike clinical disability was associated with depressive symptoms and lower HRQoL emotional subscores (β≤-0.29, p≤0.019). Depressive symptoms and apathy were associated with right temporal, left insular and right occipital lesion load (ß≥0.29, p≤0.032). Anxiety was associated with lower white matter volume (ß = -0.25, p = 0.045). Conclusion Mild depressive symptoms and anxiety with decreased HRQoL are present in patients with CIS. Neuropsychiatric symptoms contributing to decreased HRQoL are the result of structural brain changes and require complex therapeutic approach in patients with CIS.